2014
DOI: 10.1074/jbc.m113.520981
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-induced Structural Changes of Ceruloplasmin Foster NGR Motif Deamidation That Promotes Integrin Binding and Signaling

Abstract: Background: Asparagine deamidation at Asn-Gly-Arg (NGR) sites leads to the isoAsp-Gly-Arg (isoDGR) integrin-binding motif formation. Results: Ceruloplasmin (Cp), which contains two NGR sites and is oxidized in cerebrospinal fluid (CSF) in neurodegenerative diseases, can, undergo oxidation-induced structural changes fostering NGR deamidation with gain of integrin binding and signaling properties, in vitro and ex vivo in pathological CSF. Conclusion: Cp NGR motifs can deamidate acquiring integrin-binding functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 48 publications
3
69
0
Order By: Relevance
“…10; Olivieri et al, 2011). The prooxidant condition that occurs in neurodegenerative disorder CSF is underlined by the observed general increase of total protein carbonylation in CSF from PD (Iannaccone et al, 2013) and by the observation that exogenous purified Cp added and ex vivo aged for 9 days in CSF from AD patients resulted in oxidative modifications that did not occurred if aging was done in CSF of healthy subjects (Barbariga et al, 2014). Therefore, PD and AD pathological CSF contain compounds/small molecules that foster protein oxidative modifications, likely contributing to exacerbate the disorders.…”
Section: Figurementioning
confidence: 91%
See 4 more Smart Citations
“…10; Olivieri et al, 2011). The prooxidant condition that occurs in neurodegenerative disorder CSF is underlined by the observed general increase of total protein carbonylation in CSF from PD (Iannaccone et al, 2013) and by the observation that exogenous purified Cp added and ex vivo aged for 9 days in CSF from AD patients resulted in oxidative modifications that did not occurred if aging was done in CSF of healthy subjects (Barbariga et al, 2014). Therefore, PD and AD pathological CSF contain compounds/small molecules that foster protein oxidative modifications, likely contributing to exacerbate the disorders.…”
Section: Figurementioning
confidence: 91%
“…We found that both Cp NGR sites can deamidate; however, while 568 NGR is free to convert to iso-DGR (Fig. 11), the 962 NGR motif undergoes deamidation only when Asn aging occurs under oxidative conditions, in which Cp structural changes are induced, as demonstrated by circular dichroism analysis (Barbariga et al, 2014). The NGR to isoDGR transition in Cp results in a loss of ferroxidase activity and a gain in integrin-binding function (Barbariga et al, 2014).…”
Section: Oxidation-induced Structural Changes Foster Ceruloplasminmentioning
confidence: 94%
See 3 more Smart Citations